Review of Roy K. GIBSON, Man of High Empire. The Life of Pliny the Younger - Della Calce, Elisa (Ciceroniana On Line, 2024)
Review of Roy K. GIBSON, Man of High Empire. The Life of Pliny the Younger, Oxford University Press, New York 2020, 298 pp., ISBN 9780199948192.